Pengaruh Budaya dan Sosial Terhadap Keputusan Pembelian Produk Mie Instant merk Indomie (Studi pada kelurahan Telanaipura Kecamatan Telanaipura) - Denny Asmas; Ahmad Tarmizi (J-MAS (Jurnal Manajemen dan Sains), 2021)
This study aims to analyze the cultural and social influence on the purchase decision of indomie instant noodle products The results of this study revealed that cultural and social variables simultaneously and partially had a significant effect on the decision to purchase indomie instant noodle products in telanaipura village, Telanaipura subdistrict.